Zunächst vor der eigenen (Kirchen-)Tür kehren! - Peter Mandler (Wirtschaftsdienst, 2013)
Die Kirchen fordern immer wieder eine gerechtere Verteilung ein. Bei der Besteuerung ihrer eigenen Mitglieder weichen sie jedoch regelmäßig von der durch den Einkommensteuertarif vorgegebenen durchgängigen Progression ab: bei der Kirchensteuer gibt es regional unterschiedliche Kappungssätze. Nach Auffassung des Autors begibt sich die Kirche damit in Widerspruch zu dem von ihr proklamierten Verteilungsziel. – – At Easter representatives of the Roman Catholic Church and of the German Protestant Church argued for more redistribution. The main tool for redistribution in the German tax system is the progressive income tax. The most important source of funding for the church, the church tax, is directly linked to income. However, for top earners an alternative tax scale applies. In most federal states the church tax is limited to a certain percentage of taxable income, a provision known as 'capping': hence, in contrast to the throughout progressive income tax, the church tax is lowered to a proportional burden for top earners. Therefore, the churches' demands for more redistribution are inconsistent with the 'capping'. An institution that campaigns for a specific type of distribution of taxation burden should at first apply the underlying principles to its own members.
Keywords: E62; H24; Z12; 330; Kirchenfinanzierung; Einkommensteuertarif; Steuerprogression; Steuervergünstigung; Deutschland